Evaluating safety and cost‐effectiveness of platelets stored in additive solution (PAS‐F) as a hemolysis risk mitigation strategy. Issue 4 (27th December 2018) - Pagano, Monica B.; Katchatag, Brennan L.; Khoobyari, Shiva; Van Gerwen, Mark; Sen, Nina; Rebecca Haley, N.; Gernsheimer, Terry B.; Hess, John R.; Metcalf, Ryan A.
Abstract : BACKGROUND: Platelet inventory constraints can result in minor ABO incompatibility and possible hemolysis. The aims of this study were to determine the reduction of isoagglutinin in titers of platelets stored in additive solution (PAS) and compare its safety, efficiency, and cost‐effectiveness with full‐volume and plasma‐reduced platelets. STUDY DESIGN AND METHODS: Isoagglutinin titers were performed in paired whole blood donor samples and apheresis platelets collected in PAS (PAS‐PLT) aliquot samples by the tube method. RESULTS: A total of 149 pairs of donor/platelet samples were tested: 75 group O, 59 group A, and 15 group B. For group O donor samples, the median anti‐A IgG and IgM were 64 and 16, respectively, and the median anti‐B IgG and IgM were 64 and 16, respectively. For group O PAS‐PLT samples the mean anti‐A IgG and IgM, and anti‐B IgG and IgM were 32 and 8, and 16 and 8, respectively. For group A donor samples, the mean anti‐B IgG and IgM was 8 in both cases; and both titers decreased to 2 in PAS‐PLT. For group B donor samples, mean anti‐A IgG and IgM was 16 in both cases; and both titers decreased to 4 in PAS‐PLT. PAS‐PLT demonstrated a net reduction in cost and improved efficiency when compared to plasma reduction. The use of PAS‐PLT resulted in a 40% reduction of allergic transfusion reactions. CONCLUSION: The use of PAS decreases plasma isoagglutinin titers, transfusion reactions, and is cost‐effective when compared to routine plasma reduction as a strategy to mitigate hemolysis risk from minor incompatible platelet transfusion.